2015
DOI: 10.5935/medicalexpress.2015.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for overuse injuries in runners’ ankles: a literature review

Abstract: In spite of the numerous benefits to human health and given the increase of running as an exercise that has become popular worldwide, this type of sport may be the cause of a number of different injuries. The foot, ankle and lower leg comprise almost 40% of the injuries. However, the etiology of these types of injury is still not completely understood. OBJECTIVE: To investigate the causes of the onset of overuse injury in runners. METHODS: A systematic search of the electronic database was made: Bireme, Pubmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…Evidence advocates that dynamic movement patterns of the lower limb can become influenced by some intrinsic foot pathologies [5]. it has been found that bilateral foot hyper-pronation can alter pelvic positions owing to the biomechanical connections like the posterior kinetic chain mechanism [7][8][9]. As far as balance is concerned, the ankle and hip strategies are interlinked to maintain the centre of gravity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence advocates that dynamic movement patterns of the lower limb can become influenced by some intrinsic foot pathologies [5]. it has been found that bilateral foot hyper-pronation can alter pelvic positions owing to the biomechanical connections like the posterior kinetic chain mechanism [7][8][9]. As far as balance is concerned, the ankle and hip strategies are interlinked to maintain the centre of gravity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…O desequilíbrio de agonistas e antagonistas da musculatura anterior e posterior da coxa, de grau moderado a grave, foi associado ao surgimento de lesões no joelho 11 . Outras possíveis causas como a distância percorrida, o calçado utilizado, o tipo de solo de treinamento, histórico de lesões anteriores, alterações na biomecânica do movimento são fatores que contribuem para as lesões em corredores, sendo essas de origem multifatorial 10,12 . A preocupação com a prevenção e o tratamento das lesões ganhou importância na área científica, devido ao aumento significativo de lesões em praticantes deste esporte.…”
Section: Introductionunclassified